Death strikes : the emperor of Atlantis - Maass, Dave (Dark Horse Books, 2024)
"Mixing dystopian sci-fi, mythic fantasy, and zombie horror, Death Strikes: The Emperor of Atlantis, is a graphic novel based on a suppressed opera composed in 1943 by two prisoners, Peter Kien and Viktor Ullmann, at the Terezín concentration camp in Czechoslovakia. The authors did not live to see their masterpiece performed. Set in an alternative universe where Atlantis never sank but instead became a technologically advanced tyranny, the power-mad buffoonish Emperor declares all-out war--everyone against everyone. Death goes on a labor strike, creating a hellscape where everyone fights, but no one dies. Can the spirit of Life stop this terror with the power of love? Includes designs from the original opera, historical essays, photographs, and more"--